Tracking the evolution of Social Accounting: intellectual milestones, key debates and research challenges ahead - Faiz, Ali; Plaza-Navas, Miquel-Angel; Prado-Román , Miguel; Torres-Pruñonosa , Jose (REVESCO. Revista de Estudios Cooperativos, 2025)
We aim to analyze the intellectual structure, in other words, the cited references included in the citing papers that deal with social accounting, clustering them and highlighting those papers that can be considered to be either turning points (the backbone of social accounting, those that allowed the dissemination of this field of knowledge) or burst papers (those that receive a high number of citations in a short period of time). A co-citation bibliometric analysis was conducted, using CiteSpace to study the intellectual structure–24,176 cited references–contained in the 408 papers published in journals indexed in the Social Science Citation Index and in the Emerging Sources Citation Index. The study identifies twelve clusters that comprise the intellectual structure of social accounting. The results provide an overall perspective on social accounting in terms of networks and their connections, identify the most influential research areas and describe the composition of the sub-disciplines that evolved. Furthermore, papers that can be regarded as turning points are identified, as well as those that received a significant number of citations over a particular time. A research agenda is also included to help scholars to keep on analysing this increasing field of knowledge, which is being implemented in many companies when monetising social value creation. The research should be mainly focused on the standardisation of processes for identifying and accounting for social value, particularly in monetary units.
Keywords: Social accounting; social value; intellectual structure; bibliometric; trends; co-citation